2013
DOI: 10.2478/s13382-013-0082-6
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function impairment and airway allergy among workers in traditional bakeries

Abstract: Objectives: To assess the effect of exposure to flour dust on pulmonary function tests, prevalence of symptoms (respiratory, allergic/irritating) and parameters of allergic sensitization in terms of skin prick test, and bronchial hyper-responsiveness. Material and Methods: 43 bakers (with at least 2 years of occupational exposure) working at different bakeries in Ismailia city, Egypt; and 64 control subjects of comparable socio demographic characteristics were compared. All participants were subjected to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…(5)(6)(7) Exposure to flour dust can also lead to chronic bronchitis and bronchial obstruction. (8,9) High concentration periods related to specific work activities in bakeries may be decisive in causing the adverse health effects. The prevention of these periods could decrease allergic and respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…(5)(6)(7) Exposure to flour dust can also lead to chronic bronchitis and bronchial obstruction. (8,9) High concentration periods related to specific work activities in bakeries may be decisive in causing the adverse health effects. The prevention of these periods could decrease allergic and respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that occupational exposure to dust not only caused respiratory irritation and allergy but also reduced the values obtained for lung function tests including FVC, FEV 1 , FEV 1 /FVC, and FEF25-75%. [29,43,44] Moghaddasi et al comparing subjects exposed to dust for <5 years and the control group, no significant difference in terms of FEV 1 and FVC parameters was observed between the two groups. However, comparing with the control group, the mean percentage of FEV 1 and FVC was lower in those with a history of over 5 years of exposure.…”
Section: Discussionmentioning
confidence: 98%
“…According to American Thoracic Association instruction, [26][27][28][29][30][31][32] PFT include FVC, VC, FEV 1 , and PEFR. They were measured on workplaces of the workers in different shifts and to a sufficient extent using portable calibrated spirometer (Mir factory, Italy).…”
Section: Pulmonary Function Tests (Pfts)mentioning
confidence: 99%
“…An association of occupational flour dust exposure with a decreased lung function has been found in flour mill (Bagheri et al 2013;Demeke and Haile 2018;Lagiso et al 2020;Mohammadien et al 2013;Zamani et al 2019) or bakery workers (Fahim and El-Prince 2013;Moghaddasi et al 2014;Said et al 2017), as recently reviewed by Zamani (Zamani et al 2019). In these studies, the occupational flour dust exposure was solely represented by the exposure status (Fahim and El-Prince 2013;Lagiso et al 2020;Moghaddasi et al 2014;Mohammadien et al 2013), the duration of exposure (Demeke and Haile 2018;Said et al 2017), or by the atmospheric flour dust concentration at the time of the data collection (Bagheri et al 2013;Zamani et al 2019). Different spirometric parameters were affected depending on the study (Zamani et al 2019).…”
mentioning
confidence: 99%